Effect of climatic factors on the level of Coffee berry borer (Hypothenemus hampei Ferr) attack on smallholder coffee plantation in Tana Toraja Regency. Issue 4 (July 2021) - Kaimuddin,; Mustari, K; Ridwan, I; Natasya, F; Yassi, A; Bahrun, A H
Abstract: This study aims to analyze the relationship between climate parameters and the level of Coffee berry borer (CBB) ( Hypothenemus hampei Ferr) pest attack and predict the impact of climate change on the CBB pest population. The research was conducted in Tana Toraja Regency, Gandang Batu Sillanan District, Benteng Ambeso Village and Gandang Batu Village from June 2019 to July 2019. The research was in the form of survey (literature study, observation, and interviews), with purposive sampling carried out by selecting 30 respondents as the sample. Data analysis was conducted using SPSS multiple linear regression software with five variables. The area of CPB attack was the independent variable, while the maximum temperature, minimum temperature, average temperature, humidity and rainfall were the dependent variables. The multiple linear regression equation is Y = 544.292 - 7.321X1 - 15.960X2 + 24.739X3 - 356X4 + 0.005X5. The coefficient of determination obtained was an R square value of 0.609, meaning that 60.90% of the area of the CBB pest attack for coffee plants can be explained by climatic factors, while the remaining 30.10% is explained by other variables outside the variables used. Climatic factors that affect the area of CBB pest attack were minimum temperature (probability value 0.041<0.05) and the average temperature (probability value 0.027<0.05). These variables were considered to have a significant effect while the maximum temperature factor (probability value 0.121> 0.05), humidity (probability value 0.221>0.05) and rainfall (probability value 0.581>0.05) was declared to have no significant effect.